Tough and tricky Summations.

Calculus Level 5

n = 0 1 n ! [ k = 0 n ( k + 1 ) 0 1 2 ( k + 1 ) x d x ] = ? \large \sum _{ n=0 }^{ \infty }{ \frac { 1 }{ n! } \left[ \sum _{ k=0 }^{ n }{ \left( k + 1 \right) \int _{ 0 }^{ 1 }{ { 2 }^{ -\left( k + 1 \right) x }dx } } \right] } = \ ? .


The answer is 5.11.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Chew-Seong Cheong
Aug 31, 2017

S = n = 0 1 n ! [ k = 0 n ( k + 1 ) 0 1 2 ( k + 1 ) x d x ] = n = 0 1 n ! [ k = 1 n + 1 k 0 1 2 k x d x ] = n = 0 1 n ! [ k = 1 n + 1 k [ 2 k x k ln 2 ] 0 1 ] = n = 0 1 n ! ln 2 k = 1 n + 1 ( 1 2 k ) = 1 ln 2 n = 0 1 n ! ( n + 1 1 2 ( 1 2 ( n + 1 ) 1 1 2 ) ) = 1 ln 2 n = 0 1 n ! ( n + 2 ( n + 1 ) ) = 1 ln 2 ( n = 0 n n ! + 1 2 n = 0 2 n n ! ) = 1 ln 2 ( n = 1 n n ! + e 2 ) = 1 ln 2 ( n = 1 1 ( n 1 ) ! + e 2 ) = 1 ln 2 ( n = 0 1 n ! + e 2 ) = e + e 2 ln 2 5.11 \begin{aligned} S & = \sum_{n=0}^\infty \frac 1{n!} \left[\sum_{\color{#3D99F6}k=0}^{\color{#3D99F6}n}({\color{#3D99F6}k+1})\int_0^1 2^{-({\color{#3D99F6}k+1})x} dx \right] \\ & = \sum_{n=0}^\infty \frac 1{n!} \left[\sum_{\color{#D61F06}k=1}^{\color{#D61F06}n+1}{\color{#D61F06}k}\int_0^1 2^{-{\color{#D61F06}k}x} dx \right] \\ & = \sum_{n=0}^\infty \frac 1{n!} \left[ \sum_{k=1}^{n+1} k \left[-\frac {2^{-kx}}{k \ln 2} \right]_0^1 \right] \\ & = \sum_{n=0}^\infty \frac 1{n! \ln 2} \sum_{k=1}^{n+1}\left(1 - 2^{-k}\right) \\ & = \frac 1{\ln 2} \sum_{n=0}^\infty \frac 1{n!} \left(n+1 - \frac 12 \left(\frac {1- 2^{-(n+1)}}{1-\frac 12} \right) \right) \\ & = \frac 1{\ln 2} \sum_{n=0}^\infty \frac 1{n!} \left(n+ 2^{-(n+1)}\right) \\ & = \frac 1{\ln 2}\left(\sum_{\color{#3D99F6}n=0}^\infty \frac n{n!} + \frac 12 \sum_{n=0}^\infty \frac {2^{-n}}{n!} \right) \\ & = \frac 1{\ln 2}\left(\sum_{\color{#D61F06}n=1}^\infty \frac n{n!} + \frac {\sqrt e}2 \right) \\ & = \frac 1{\ln 2}\left(\sum_{\color{#D61F06}n=1}^\infty \frac 1{(n-1)!} + \frac {\sqrt e}2 \right) \\ & = \frac 1{\ln 2}\left(\sum_{\color{#3D99F6}n=0}^\infty \frac 1{n!} + \frac {\sqrt e}2 \right) \\ & = \frac {e+\frac {\sqrt e}2}{\ln 2} \approx \boxed{5.11} \end{aligned}

Why is this listed as an Algebra problem? Should be a Calculus one instead.

tom engelsman - 3 years, 9 months ago

Log in to reply

Thanks, I have changed it.

Chew-Seong Cheong - 3 years, 9 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...